PONM16 Unusual surgery for progressive finger-drop. Issue 11 (22nd October 2010) - Khan, U; Murphy, S; Lunn, M; Hrouda, D; Seckl, M; Ball, J; Alifrangis, C; Gabriel, C; Hazel, S; Reilly, M M
Abstract : We present the case of a 46-year-old dentist who noticed weakness of pincer movement of the left hand whilst at work. Six weeks later, he developed progressive finger-drop affecting the left hand over days and then the right hand over weeks. Over this period, he reported altered sensation spreading across his shoulders and back. Five years previously, he had been treated successfully for seminoma with orchidectomy alone and had normal follow-up assessments. Abnormal examination findings were restricted to his upper limbs with bilateral wasting of shoulder-girdle, arm and forearm muscles more marked distally, some fasciculations, but preserved reflexes and marked bilateral finger-drop. General physical examination was normal. EMG suggested a severe motor neuropathy or neuronopathy affecting the cervical regions. Detailed brain and spine neuroimaging was normal. PET scanning and testicular ultrasound were normal. Oligoclonal bands were positive in the CSF only. Extensive blood tests for infection and inflammation were normal. He was initially managed for inflammatory motor neuropathy until the result of one blood test which led to an unusual surgical procedure being sought for his further management. This case represents a unique presentation of a rare neurological syndrome and illustrates the expanding clinical spectrum associated with this syndrome.